Relationship between performance characteristics and the selection process in youth soccer players - Lago-Penas, C.; Rey, E.; Casáis, L.; Gómez-López, M. (Journal of Human Kinetics, 2014)
The purpose of this study was to establish the anthropometric and physical profiles of elite young soccer players according to their playing position, and to determine their relevance for the selection process. One hundred and fifty-six young male soccer players participated in the study. Players were classified into the following groups: Goalkeepers (n=16), Central Defenders (n=26), External Defenders (n=29), Central Midfielders (n=34), External Midfielders (n=28), and Forwards (n=23). Anthropometric variables of participants (body height, body mass, body mass index, 6 skinfolds, 4 diameters, and 3 perimeters) were measured. Participants performed the Yo-Yo test, sprint tests (30 m flat sprint and Balsom agility test) and 2 jump tests (countermovement jump and the Abalakov test). At the end of the season, the technical staff of the club selected some of the players to continue playing on the same team and the rest were not selected. The results show that heavier and taller outfield players performed better in vertical jumps and sprint tests, whereas leaner outfield players performed better in the Yo-Yo test. Fat percentage of selected players was lower than that of the non-selected ones. The rest of the body components were similar in the selected and non-selected players within each playing position. Moreover, the selected players performed slightly better than the non-selected players in the physical test, but these differences were not statistically significant.